NCOG-23. PATTERNS OF DISTRESS IN OLDER PATIENTS WITH GLIOBLASTOMA: A FOLLOW-UP TO A SINGLE INSTITUTION CROSS-SECTIONAL STUDY OF DISTRESS IN PRIMARY BRAIN TUMOR PATIENTS. (9th November 2020) - Johnson, Margaret; Herndon, James; Lipp, Eric; Affronti, Mary; Desjardins, Annick; Bhattacharya, Manisha; Friedman, Henry; Ashley, David; Peters, Katherine; Randazzo, Dina
Abstract: INTRODUCTION: We previously reported to SNO, high levels of psychosocial distress in adult patients with primary brain tumors (PBTs), particularly during the first 6 months following diagnosis. The purpose of this follow-up study was to identify patterns of distress among older (≥ 65 years) patients with glioblastoma (GBM) compared to their younger (ages 18-64) counterparts. METHODS: In our initial cross-sectional study, we collected the National Comprehensive Cancer Network's Distress Thermometer (NCCN-DT) and problem list from adult patients with PBTs (WHO grades I-IV) seen at our institution between December 2013 and February 2016. We performed subsequent analyses on a subset of patients with GBM. RESULTS: We identified 343 patients with GBM from the original dataset, of which 23.0% (n= 78) were ≥ 65 years old. The proportion of patients ≥ 65 years old with elevated distress (i.e. DT ≥ 4) was greater than the proportion of younger patients reporting elevated distress (47.4% vs 30.6%; p= 0.0068). Elevated distress was significantly greater during the first 6 months post diagnosis for all ages (p= 0.008). In subgroup analyses, a decrease in distress beyond 6 months was seen in younger patients (45.7% vs 27.4%; p= 0.021), but not in older patients. In older patients, a greater number of problems were selected on the NCCN DT and problem list tool: emotional and physical concerns were reported more frequently compared to their younger counterparts. Older patients were more likely to report difficulty with "bathing" and "getting around" (p= 0.009, p< 0.001, respectively). There were no differences in older versus younger GBM patients with regard to housing, transportation, treatment decisions, depression, fatigue, or memory. CONCLUSIONS: In contrast to their younger counterparts, older patients with GBM experienced elevated levels of distress and a greater absolute number of specific psychosocial problems, mostly related to emotional and physical concerns.